The river wild [videorecording (DVD)] - Hanson, Curtis; Streep, Meryl; Bacon, Kevin, 1958-; Straitharn, David; Goldsmith, Jerry (Universal Studios Home Video, 1992)
Escaping bank robbers kidnap a vactioning family, rafting down scenic whitewater rivers. The mother struggles to comply while looking for a way out.